Odpowiedzi

Najlepsza Odpowiedź!
2009-12-15T16:48:15+01:00
{2x-3y=7 / * (3)
{3x-5y=11 / * (-2)

Korzystamy z metody przeciwnych wsółczynników:
{6x-9y=21
{-6x+10y=-22
0 +1y=-1
y=-1

{2x-3y=7
{y=-1

2x+3=7
y= -1

2x=4
y=-1

x=2
y=-1



2009-12-15T16:48:57+01:00
{2x-3y=7/*5
{3x-5y=11/*(-3)

10x-15y=35
-9x+15y=-33

x=2
10x-15y=35

x=2
10*2-15y=35

x=2
20-15y=35

x=2
-15y=35-20

x=2
-15y=15 /:(-15)

x=2
y=-1

2009-12-15T16:51:43+01:00
{2x-3y=7|*5
{3x-5y=11|*-3
{10X -15y=35
{-9x+15y=-33
x=2
{2*2-3y=7
{4-3y=7
-3y=7-4
-3y=3/:-3
y=-1
x=2